Four Important Poisonous Fishes in the Black Sea Coasts: Some Biological Features and Length-Weight Relationships - Yakup Erdem; Süleyman Özdemir; Ferhat Buyukdeveci; Uğur Özsandıkçı (Journal of New Results in Science)
In this study were demonstrated length-weight relationships (LWRs) and some biological characteristic of four venomous fishes from Black Sea coasts. The most important venomous fish in the Black Sea coasts are common stingray (Dasyatis pastinaca), greater weever (Trachinus draco), scorpion fish (Scorpaena porcus) and stargazer (Uranoscopus scaber). The present study was carried out between 01 January 2015 and 30 September 2016 in Sinop peninsula coasts of the southern Black Sea. The fish samples were captured trammel nets (32 mm, 36 mm 40 mm and 48 mm mesh size) in 0-15-30-45 meters depth ranges. The average length of common stingray, greater weever, scorpion fish and stargazer were established 48.2±4.98 cm 17.88±0.25 cm, 11.49±0.07 cm, 13.25±0.47 cm and respectively. LWR of the venomous fishes were determined W=0.0028L3.2187 (n=12, R2=0.97), W=0.0287L2.5776 (n= 181, R2=0.93), W=0.0245L2.9050 (n=808, R2=0.98) and W=0.0181L2.9398 (n=779, R2=0.98) and respectively. Positive allometric growth for common stingray and negative allometric growth for greater weever, scorpion fish and stargazer were obtained (t-test, p < 0.05).